2010
DOI: 10.1645/ge-2379.1
|View full text |Cite
|
Sign up to set email alerts
|

Parasites Found From the Feces of Bornean Orangutans in Danum Valley, Sabah, Malaysia, with a Redescription of Pongobius hugoti and the Description of a New Species of Pongobius (Nematoda: Oxyuridae)

Abstract: In order to obtain basic data on parasitic infections of Bornean orangutans, Pongo pygmaeus morio (Owen, 1837), in Danum Valley, Sabah, Malaysia, fecal examinations were conducted. Based on a total of 73 fecal samples from 25 individuals, cysts of Entamoeba coli, Entamoeba spp., and Chilomastix mesnili, cysts and trophozoites of Balantidium coli, and eggs of Trichuris sp. or spp., unknown strongylid(s), Strongyloides fuelleborni, and an unknown oxyurid, plus a rhabditoid larva of Strongyloides sp., were found.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 13 publications
4
30
2
2
Order By: Relevance
“…Two major groups (protozoan and helminths) and four classes from the helminths group, namely nematodes, cestodes, trematodes, and pentastomida were major taxa groups of GI parasites that infect NHP during this study. This current finding is consistent with those reported as infecting NHP species in Malaysia and worldwide . Thus, all taxa groups recorded in this study were common groups infecting NHP and other animals including humans.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Two major groups (protozoan and helminths) and four classes from the helminths group, namely nematodes, cestodes, trematodes, and pentastomida were major taxa groups of GI parasites that infect NHP during this study. This current finding is consistent with those reported as infecting NHP species in Malaysia and worldwide . Thus, all taxa groups recorded in this study were common groups infecting NHP and other animals including humans.…”
Section: Discussionsupporting
confidence: 92%
“…Gastrointestinal parasites have been reported in previous studies, among them NHP species, N. coucang , M. arctoides , M. fascicularis , M. nemestrina , N . larvatus , T. cristatus , T. obscurus , H. lar , S. syndactylus, and P. pygmaeus , except for P. rubicunda and H. agilis . Thus, this study showed the first report on the examination for GI parasites for P. rubicunda and H. agilis .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…(Gillespie et al 2009 ;Hogan et al 2014 ;Sak et al 2014 ;Parsons et al 2015). Bien que la plupart des espèces d'amibes infectant les grands singes ne soient pas pathogènes, il y a quelques exceptions : Entamoeba histolytica et Neobalantidium coli ont été décrites chez différents primates circulant librement, y compris des chimpanzés, des gorilles et des orangs-outans qui partagent le même habitat que l'homme (Mul et al 2007 ;Gillespie et al 2010 ;Kuze et al 2010 ;Hassell et al 2013 ;Zommers et al 2013).…”
Section: Maladies Parasitairesunclassified